Asymmetric A–D–π–A-type nonfullerene small molecule acceptors for efficient organic solar cells. Issue 33 (7th August 2019) - Li, Xueshan; Li, Chao; Ye, Linglong; Weng, Kangkang; Fu, Huiting; Ryu, Hwa Sook; Wei, Donghui; Sun, Xiaobo; Woo, Han Young; Sun, Yanming
Abstract : By applying a rational molecular cutting strategy to the indacenodithienothiophene (IDTT) skeleton, a novel asymmetric A–D–π–A type acceptor, TTPT-T-2F, was developed. Abstract : There has been significant progress with regard to research on nonfullerene small molecule acceptors (SMAs) during the past several years. Typically, high-performance nonfullerene SMAs are based on symmetric A–D–A or A–π–D–π–A structural frameworks. In this study, a novel asymmetric nonfullerene SMA, TTPT-T-2F, with an A–D–π–A structure is rationally designed and synthesized. In addition, a symmetric A–D–A-type nonfullerene SMA, IT-2F, and a symmetric A–π–D–π–A-type nonfullerene SMA, T-TPT-T-2F, are also synthesized for comparison. When PBT1-C is employed as a polymer donor, a promising power conversion efficiency (PCE) of 12.71% is achieved for TTPT-T-2F-based organic solar cells (OSCs), which surpasses those of devices based on IT-2F (PCE = 10.54%) and T-TPT-T-2F (PCE = 10.71%). Favorable phase separation toward efficient and more balanced charge transport accounts for the higher PCE achieved in the PBT1-C:TTPT-T-2F device. Our results demonstrate that a small molecule acceptor with an A–D–π–A structural framework is a promising class of nonfullerene acceptors for OSCs.